2014
DOI: 10.1080/14786419.2014.888553
|View full text |Cite
|
Sign up to set email alerts
|

Antiurease activity of plants growing in the Czech Republic

Abstract: The antiurease activity of the aqueous extracts of 42 plants growing in the Czech Republic was investigated. A phenol-hypochlorite reaction was used for the determination of ammonia produced by urease. The inhibitory activity of the extracts at a concentration of 0.2 mg/mL varied from 17.8% to 80.0%. Extracts from six Potentilla species expressed inhibitory activity against jack bean urease. They were further investigated for their phenolic constituents and the major compounds were subjected to molecular docki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Urease, an enzyme catalyzing the decomposition of urea into carbon dioxide and ammonia, is one of the virulence factors of many bacteria, among them Helicobacter pylori . As was observed in computational studies (Hřibová et al., ), tiliroside can be a strong inhibitor of urease, with a docking score equal to ‐8.9 kcal/M. However promising, this outcome should be confirmed by further studies.…”
Section: Biological Activities Of Tilirosidementioning
confidence: 72%
“…Urease, an enzyme catalyzing the decomposition of urea into carbon dioxide and ammonia, is one of the virulence factors of many bacteria, among them Helicobacter pylori . As was observed in computational studies (Hřibová et al., ), tiliroside can be a strong inhibitor of urease, with a docking score equal to ‐8.9 kcal/M. However promising, this outcome should be confirmed by further studies.…”
Section: Biological Activities Of Tilirosidementioning
confidence: 72%
“…Such studies, for example, revealed that B-type PCs (catechin dimers) inhibit urease because, according to their docking scores (−6.9 kcal/mol), they fit the binding pocket of the bacterial enzyme, being these interactions energetically favorable (48). Then, molecular docking could contribute to elucidate the interactions between PCs and other cellular or bacterial targets of interest for the protection of the gastric mucosa against H. pylori .…”
Section: Pacs In the Stomachmentioning
confidence: 99%
“…mechanism-based directed, they affect the catalysis that leads to enzymatic inactivation; several plant-derived urease inhibitors have been described. 8,9 Screening and confirmation studies have demonstrated urease inhibitory activity in gastrointestinal and urinary tract by traditional medicinal plants from China, 10 Pakistan, 11 Iran, 12 Czech Republic, 13 India, 14 and other countries.…”
Section: Introductionmentioning
confidence: 99%